(untitled) (Jurnal Intek Akuakultur, 2020)
The study was conducted using a complete randomized design with 5 treatments and 3 repeats. The lighting used is control (natural light), B (white LED), C (red LED), D (green LED), and E (blue LED). The best research result ison C treatment with exposure using red LED light with a period RGB value on red Head (21,78), red Body (24,89) and 23 red tail. Parameter RGB value red color treatment on the head, body and tail of the Tiger barb best value is in the treatment C with a value of head (21,78), body (24,89) and tail (23).